Hubungan Tingkat Pengetahuan dengan Peran Keluarga terhadap Imunisasi Dasar pada Bayi Umur 0-12 Bulan: The Relationship of Knowledge Level with Family Roles on Basic Immunization in Infants Aged 0-12 Months - Mujahadatuljannah Mujahadatuljannah; Lelly Oktarina; Irfan Eka Wahyu (Jurnal Surya Medika (JSM), 2022)
Immunization is an intervention aimed at preventing and reducing major diseases such as bacteria and viruses that cause death in children. One of the factors for the low immunization coverage is the mother's fear and concern for the occurrence of An Adverse event following immunization (AEFI), including swelling and abscesses at the injection site. The need and importance of knowledge and the family's role in improving family members' health status, especially regarding basic immunizations given to their children. This study aims to determine the relationship between the mother's knowledge and the role of the family in basic immunization in infants aged 0-12 months. This research uses correlational research with a cross-sectional approach. The sample of this study was 30 respondents with a sampling technique using purposive sampling. The results of the study using the Spearman rank test showed a relationship between the level of knowledge and the role of the family in basic immunization for infants aged 0-12 months with a p-value = 0.001. In conclusion, there is a relationship between the level of knowledge and the role of the family in basic immunization in infants aged 0-12 months.